Espaços brincantes: um olhar reflexivo para os espaços utilizados para brincadeiras na contemporaneidade - Ferreira, Sônia Maria (2018)
The purpose of this research was to identify and to reflect on the contemporary spaces for games. The target audience was the students of 5th Grade / 2016, of the Municipal School Professor Sérgio de Oliveira Marquez, of the city of Uberlândia, state of Minas Gerais, Brazi. Faced with the material raised, it was noticed the reduction of space for games that occurred in the last decades due to the social changes, among which we can mention the population increase and the flow of vehicles, more and more intense, in the cities. In addition, as a practical proposal was made an intervention in the schoolyard by means of paintings on the floor and the wall, increasing the possibilities of using this space. The theme chosen was due to the perception of these changes in the students' daily lives, as well as to enable an approach between art and life, since the subject draws the attention of the students naturally, because it is part of their everyday life. It is a reflection on the importance of playing, not only in childhood and in the teaching-learning process in Art, but in all moments of human life, beginning with the need to think better about the spaces available for education.